(untitled) (Docentes 2.0 Journal, 2021)
Together with the first manipulator robot, the UNIMATE from Devol and Engelberger, the concern of researchers and engineers was born to demonstrate the potential of similar robots in industrial applications. Consequently, many prestigious universities perceived how important it was to include subjects in curricula of careers such as Electrical Engineering, Electronics, Mechanics, or Mechatronics. The present investigation was under a mixed methodology. The analysis of results is supported by the response observed in a simulator through the combined use of a Toolbox for kinematic modeling of robots (based on executable scripts in an environment such as GNU Octave or similar). Of software for 3D simulation. The modeling of the use of the tools and the challenge to the student of programming virtual IRs in typical manufacturing, packaging, or palletizing scenarios, has been tested over four academic periods, obtaining positive feedback from those approved and graduates. The results achieved when simulating demonstrate the accuracy of the kinematic models obtained through mathematical formulations, which shows the usefulness of the tools described for distance learning based on practice.